Program Badan Penyelenggara Jaminan Sosial (BPJS) Kesehatan sebagai Salah Satu Bentuk Pelayanan Publik - Ade Rizky Anantya; Natalia Cristina Saragih; Oktaviani Lumban Raja; Berlianti Berlianti (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2024)
The Social Security Administration Agency (BPJS) Kesehatan is one of the Indonesian government's initiatives in providing fair and equitable access to health services for all citizens. As a form of public service, BPJS Kesehatan aims to provide health protection through social security, increase public awareness of the importance of health, and meet the demands for quality services. By transforming several state-owned enterprises, BPJS Kesehatan plays an important role in reducing financial risks for people facing health problems. This study explores the implementation and effectiveness of the BPJS Kesehatan program in improving access and quality of public services.